Integrating environmental awareness local wisdom for developing BIPA flipbooks (project-based learning) - Chyntia Heru Woro Prastiwi; Neneng Rika Jazilatul Kholidah; Norita Prasetya Wardhani; Zalfa Shabrina; Prima Bintang Arlinanda (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Almost every region in Indonesia has its own local wisdom for environmental conservation. These local wisdoms can serve as valuable language material for teaching BIPA (Bahasa Indonesia bagi Penutur Asing, or Indonesian for Foreign Speakers). Incorporating local wisdom into BIPA lessons offers many benefits, such as providing authentic learning experiences, enhancing socio-cultural awareness, fostering character development, improving language skills, and promoting tolerance and mutual respect. Local wisdom can be a powerful asset or bargaining chip in engaging with the global community. This research developed flipbooks for BIPA using local wisdom for environmental awareness through a project-based learning approach. Following a research and development (R&D) design, the researchers created 12 flipbooks for BIPA beginner level, each featuring local wisdom related to environmental preservation, such as Subak-Bali, Mentari Bondar-Tapanuli, Paca Goya-Tidore, Buka Egek-Papua, Sasi-Maluku, Kapal Pinisi-Sulawesi, Taman Laut Karimunjawa-Jepara, Merti Code, Wiwitan, Sedekah Bumi, Nyadran, and Kirab Budaya from Java. They integrated the local wisdom in terms of photo, picture, text, and audio-lingual media for speaking, listening, reading, and writing language activities. However, this research only covered three stages of the ADDIE model for developing BIPA flipbooks: analysis, design, and development. The implementation and evaluation stages have not been conducted yet, due to the time constraints of waiting for foreign users in online clicking the flipbooks as well as expert feedback.